Efeitos do tratamento com análogos do GNRH sobre o índice de massa corpórea em pacientes com puberdade precoce dependente de gonadotrofinas - SILVA, Laercio Dezinho da (2023)
INTRODUCTION: The effect of GnRH agonists(aGnRH), main course of treatment in Gonadotrophin-dependent Precocious Puberty, on the BMI and risk of developing obesity has been the subject of several studies with controversial results. OBJECTIVES: Assess the effect of aGnRH on the weight and BMI of Gonadotrophin-dependent Precocious Puberty patients over the first and second years of treatment. METODHOLGY: This is an epidemiological, individualized, observational and retrospective longitudinal study. Data collection took place in four stages: (1) selection of medical records; (2) review of medical records; (3) recording the data. After the selection of the medical records, the demographic data (sex and chronological age), clinical, hormonal, bone age and anthropometric data were recorded before treatment with any drug at the first visit 6, 12 and 24 months after starting treatment with aGnRH. RESULTS: The study analyzed 82 patients of both sexes, 78 girls and 4 boys, diagnosed with gonadotrophin-dependent PP, who initially presented mean age of 8.1 ± 1.5 years and mean BMI of 18.6 ± 2.7 kg / m², submitted to aGnRH treatment. It was observed that 52% of the individuals had above-normal Z-BMI for chronological age. Patients were observed for weight, height, BMI and Z-BMI over 2 years of aGNRH treatment. No statistically significant difference was found when we compared the baseline Z-BMI versus 1 year versus 2 years of treatment. CONCLUSION: There was no change in the Z-BMI over 2 years of treatment with aGnRH on patients with gonadotrophin-dependent Precocious Puberty. However, the patients with normal weight and BMI before treatment had a significant increase in Z-BMI in the first year of treatment. By the end of the second year, this difference was not found.